Scientific Understanding of the Induced Membrane Technique: Current Status and Future Directions. Issue 5 (October 2017) - Yee, Michael A.; Mead, Matthew P.; Alford, Andrea I.; Hak, David J.; Mauffrey, Cyril; Hake, Mark E.
Abstract : Objectives: To review the most recent basic science advances made in relation to the induced membrane technique and how those relate to clinical practice, applications, and future research directions. Design: Review of the literature. Setting: Any trauma center which might encounter large segmental bone defects. Articles Reviewed: Basic science articles that looked at characteristics of the induced membrane published in the past 30 years. Intervention: None.